Kinesio taping versus athletic taping in managing chronic golfer`s elbow in male athletes - Abdelmonem, A. F.; Ameer, M. A.; Ghuiba, K.; Al Abbad, A. M. (International Journal of Athletic Therapy & Training, 2022)
Medial epicondylalgia is a repetitive stress condition. The aim of this study was to assess whether Kinesio taping offers any superiority over athletic taping for chronic medial epicondylalgia management. The results show statistically significant differences in isokinetic and patient self-reported variables between each group: (a) Group A: Kinesio tape with rehabilitation; (b) Group B: athletic taping with rehabilitation; and (c) group C: only rehabilitation. Although no significant differences in preintervention group assessments (p > .05) were found, only Group (A) showed statistically significant posttreatment improvements. Kinesio taping over athletic taping appears effective for treating chronic medial epicondylalgia and facilitating pain reduction and isokinetic improvements.